Snow Compaction in Construction of Snow Roads for Motor Vehicles - Vaisberg,I. S. (1973)
For the purpose of determining the most efficient methods of heat processing of snow and for specifying the parameters of vibrating compaction when building snow roads with snow compacting machines, the All-Union Research Institute of Road-Building Machines conducted tests for which experimental thermal-vibrating equipment was designed and manufactured. The unit consists of cutting-heating equipment, operates coupled to tractor T-100M and makes a snow covering in one pass. The cutting-heating device, including a power-operated toothed cutter and heating equipment, provided two methods of conducting hot gases to the snow. Trans. of Stroitelnye i Dorozhnye Mashiny (USSR) n10 p13-14 1971.